2017
DOI: 10.1056/nejmoa1709684
|View full text |Cite|
|
Sign up to set email alerts
|

Overall Survival with Combined Nivolumab and Ipilimumab in Advanced Melanoma

Abstract: BACKGROUND Nivolumab combined with ipilimumab resulted in longer progression-free survival and a higher objective response rate than ipilimumab alone in a phase 3 trial involving patients with advanced melanoma. We now report 3-year overall survival outcomes in this trial. METHODS We randomly assigned, in a 1:1:1 ratio, patients with previously untreated advanced melanoma to receive nivolumab at a dose of 1 mg per kilogram of body weight plus ipilimumab at a dose of 3 mg per kilogram every 3 weeks for four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
2,599
13
77

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,886 publications
(2,752 citation statements)
references
References 15 publications
63
2,599
13
77
Order By: Relevance
“…Firstly, the websites were grouped according to their providers: (1) commercial and pharmaceutical companies, (2) non-commercial/charity providers, (3) medical or scientific providers, (4) general public press, (5) commercial health information services, (6) clinics or health professionals, and (7) Wikipedia.org. The categorization was conducted independently by two researchers (JB, TS); disagreements were discussed and remedied in a subsequent meeting.…”
Section: Grouping Of Websitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the websites were grouped according to their providers: (1) commercial and pharmaceutical companies, (2) non-commercial/charity providers, (3) medical or scientific providers, (4) general public press, (5) commercial health information services, (6) clinics or health professionals, and (7) Wikipedia.org. The categorization was conducted independently by two researchers (JB, TS); disagreements were discussed and remedied in a subsequent meeting.…”
Section: Grouping Of Websitesmentioning
confidence: 99%
“…Approvals of new effective therapies in the last decade have substantially expanded the treatment spectrum, especially for melanoma patients with metastatic disease. One of these treatment options is immunotherapy, whose application has resulted in pioneering response rates and significantly increased survival chances of melanoma patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The overall survival rate at 3 years was 58% in the combination group, 52% in the nivolumab group and 34% in the ipilumimab group (4). Treatment-related adverse effects were significantly higher with combination therapy, with grade 3/4 adverse events occurring in 59% of patients in the combination group, 21% on single agent nivolumab and 28% on ipilumimab alone (4). As a result of this trial a number of patients are now being commenced on combination immunotherapy in the first line setting.…”
Section: Discussionmentioning
confidence: 94%
“…To put these results into perspective, it will help to consider the results from a Phase III study of ipilimumab plus nivolumab as compared with nivolumab alone for melanoma [12]. That pivotal study reported 58% objective response rate with the combined immunotherapy, compared with 44% with single-agent nivolumab.…”
Section: Nibit-meso1mentioning
confidence: 99%